ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA SMK KELAS X PADA MATERI SITEM PERSAMAAN LINIER DUA VARIABEL (SPLDV) - Nugi Apria; Wahyu Setiawan (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to find and analyze student errors in students' problem-solving abilities when solving questions on the SPLDV material. The subjects of this study were 10 students in class X at West Bandung Regency Vocational High School using descriptive quantitative methods which were carried out through WhatsApp groups (WAG) where data processing using Ms. Excel. Based on the results of the analysis of the percentage of completeness in this study, it is known that the level of students' mathematical problem solving is in the medium category. Therefore, the researcher can conclude that further research is needed in the future on students' mathematical problem solving abilities with the aim of producing data that can be used as evaluation and analysis material to produce a learning model that can improve mathematical problem solving abilities.